Analisis Lingkungan Eksternal dan Internal (Swot dan Pestel) - Putri, Anjellie Dasviana; L, Lisaryadi; J, Jamrizal; Aprianto, Iwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Educational Strategic Management is a process designed in achieving performance improvement in educational institutions. On this process will involve formulating a vision, mission, as well as goals and analyzing the external as well as internal environment. To that end, then in this paper the author will discuss regarding the analysis of external and internal environment in strategic management of education. External environmental analysis is the effort made by an educational organization to pay attention to and emphasize the role of the external environment that can affect the educational institution. Internal environment analysis is an attempt to recognize the internal and external factors that influence the achievement of an institution’s goals. This involves an assessment of all the possibilities and limitations possessed by the institution. SWOT analysis is a method of planning models, strategies, and business development used to assess the strengths (strengths), weaknesses, opportunities, and threats in a project or business speculation. These four elements form the acronym SWOT (strengths, weaknesses, opportunities, threats). The SWOT approach includes setting specific goals of a business venture or project as well as identifying internal and external factors that support or hinder the achievement of those goals. PESTEL Analysis (PESTLE Analysis) is a technique in strategic management which is used to look at the external/external environmental factors of a business or institution that influence the Institution. These factors include the areas: Political (Political), Economic (Economics), Social (Social), Technological (Technology), Legal (Legal), and Environment (Environment).